Climate change, differential impacts on women and gender mainstreaming: a case study of East Rapti Watershed, Nepal - Ray, A.; Pandey, Vishnu Prasad; Dongol, R. (2022)
Women and water share a great deal of nexus in several ways. However, women have still minimal control over the management of water resources, making them more vulnerable to climate change. This paper assesses how climate change impacts differently across different women groups using an intersectionality lens, thereby exploring the situation of gender mainstreaming in water sector in three communities, namely, Karaiya, Basauli, and Dadagaun in Khairahani Municipality located in the East Rapti watershed, Nepal. In this perception- based study, we conducted three key informant interviews and household interviews with 45 women of different castes, ages, communities, education levels, and occupations. The results showed that different groups of women perceive climate change and its impact differently. For instance, women engaged in agriculture are more aware of the impact of climate change and are affected more by it because of changing trends in rainfall and temperature resulting in water shortage and flooding. On the other hand, they experience more physical and mental stress because of a higher responsibility of both agriculture and household . Despite 80% of female involvement in water user committees, there is a gap in participation by all groups of women. Irrespective of literacy and work engagement, women of Karaiya and Basauli, were less aware and active than Dadagau in various water development and management activities because of time constraints, family background, lesser interest, and awareness. Therefore, more efforts are required to achieve significant progress in gender mainstreaming considering intersectionality in the water sector and climate change.